Thermo-sensitive coating composition and application thereof in preparation of thermo-sensitive paper

By adding AlN/CNT thermally conductive particles to the thermally sensitive coating of the thermally sensitive paper to form a composite thermally conductive network, the problem of slow color development process of existing thermally sensitive paper is solved, and the effect of faster, uniform and clearer color development is achieved, and the durability and scratch resistance of the coating are improved.

CN120119494APending Publication Date: 2025-06-10JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510290931.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The color rendering process of existing thermal papers is slow, which affects the color rendering clarity and has a high color rendering temperature threshold.

Method used

AlN/CNT thermally conductive particles are used to form a composite thermally conductive network, and the thermally conductive particles are evenly dispersed through amide bonding and polydopamine coating, reducing thermal resistance and accelerating heat transfer.

Benefits of technology

The color rendering is faster, uniform and clear, lowers the color rendering temperature threshold, and improves the coating's moisture resistance, oxidation resistance and scratch resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005308606210000041
    Figure BDA0005308606210000041
  • Figure BDA0005308606210000051
    Figure BDA0005308606210000051
  • Figure BDA0005308606210000071
    Figure BDA0005308606210000071
Patent Text Reader

Abstract

The invention discloses a thermosensitive coating composition and application thereof in preparation of thermosensitive paper, the thermosensitive coating composition comprises the following components in parts by weight: 9-15 parts of leuco dye, 27-30 parts of a color developing agent, 10-12 parts of an adhesive, 8-10 parts of a thermosensitive sensitizer, 5-8 parts of water and 2-8 parts of AlN / CNT heat conducting particles; wherein the AlN / CNT heat conduction particle comprises an AlN / CNT composite particle inner core bonded through an amido bond and a PDA shell layer coated outside the inner core. AlN / CNT heat conduction particles (aluminum nitride / carbon nanotube heat conduction particles) are adopted to form a composite heat conduction network to accelerate heat transfer, the color development temperature threshold value is reduced, and color development is faster, more uniform and clearer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermosensitive coating composition and its application in the preparation of thermosensitive paper, belonging to the technical field of thermosensitive paper. Background Art

[0002] Thermosensitive paper is a special paper widely used in fields such as bill printing and label printing. Its core characteristic is that the thermosensitive coating produces a color reaction through a thermal reaction, resulting in a color change after being heated. However, the color development temperature threshold of the color former is generally relatively high, making the color development slower and affecting the color development clarity. Summary of the Invention

[0003] The purpose of the present invention is to provide a thermosensitive coating composition and its application in the preparation of thermosensitive paper. By using AlN / CNT thermal conductive particles (aluminum nitride / carbon nanotube thermal conductive particles) to form a composite thermal conductive network to accelerate heat transfer (reduce thermal resistance), the color development temperature threshold is reduced, making the color development faster, more uniform, and clearer.

[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] A thermosensitive coating composition, comprising the following components in parts by weight: 9 - 15 parts of a colorless dye, 27 - 30 parts of a color former, 10 - 12 parts of an adhesive, 8 - 10 parts of a thermosensitive sensitizer, 5 - 8 parts of water, and 2 - 8 parts of AlN / CNT thermal conductive particles;

[0006] Among them, the AlN / CNT thermal conductive particles include an AlN / CNT composite particle core bonded by an amide bond and a PDA shell layer coated outside the core.

[0007] Preferably, the preparation method of the AlN / CNT thermal conductive particles is: first hydroxylate AlN and carboxylate CNT;

[0008] Then disperse the hydroxylated AlN in a solution containing an amino siloxane, heat and react, and then centrifuge, wash, and dry to obtain amino-functionalized AlN;

[0009] Then mix the amino-functionalized AlN with the carboxylated CNT and an EDC / NHS crosslinking agent, stir and react, and then centrifuge, wash, dry, and pulverize and sieve to obtain an AlN / CNT composite particle bonded by an amide bond;

[0010] Finally, disperse the AlN / CNT composite particles in a buffer solution containing dopamine hydrochloride, stir, and then centrifuge, wash, and dry in an oven.

[0011] Preferably, the addition ratio of hydroxylated AlN, amino silicone, carboxylated CNT and EDC / NHS crosslinking agent is (2 - 10) g : (0.2 - 2) g : (1 - 5) g : (40 - 100) ml;

[0012] Among them, the molar ratio of EDC to NHS in the EDC / NHS crosslinking agent is 1 : (0.5 - 1.5).

[0013] Preferably, the amino silicone is 3 - aminopropyltriethoxysilane or γ - aminopropyltrimethoxysilane.

[0014] Preferably, the conditions for the heating reaction are: 60 - 90 °C, 4 - 8 h;

[0015] The conditions for the stirring reaction are: at room temperature, 300 - 1000 rpm, 8 - 15 h.

[0016] Preferably, the concentration of dopamine hydrochloride is 5 - 20 g / L, and the dosage ratio of the AlN / CNT composite particles to the buffer solution containing dopamine hydrochloride is (3 - 10) g : (300 - 1000) ml.

[0017] Preferably, the components of the binder are as follows: polyvinyl alcohol 35 - 50 wt%, acrylate emulsion 20 - 40 wt%, solvent 10 - 20 wt%, crosslinking agent 3 - 5 wt%, thickener 0.5 - 1 wt%, dispersant 0.2 - 0.5 wt%. Among them, the solvent is selected from one or a mixture of ethanol and isopropanol; the crosslinking agent is selected from one or a mixture of waterborne polyurethane, carbodiimide, and triallyl isocyanurate; the thickener is preferably hydroxyethyl cellulose (HEC), and the dispersant is preferably sodium polyacrylate.

[0018] The application of any of the above - mentioned thermosensitive coating compositions in the preparation of thermosensitive paper includes the following steps:

[0019] S1. Coating the binder on a paper base (a high - quality degradable paper after calendering, with the moisture content controlled at 5 - 7%) and drying to form an inner binder layer;

[0020] S2. Then coating the thermosensitive agent prepared from the thermosensitive coating composition (the components are mixed and sheared and dispersed by a high - speed shearer for 10 - 20 min) on the surface of the inner binder layer and drying to form a thermosensitive coating;

[0021] S3. Then coating another layer of binder on the surface of the thermosensitive coating and drying to form an outer binder layer;

[0022] S4. Finally, coating a protective agent on the outer binder layer and drying to form a protective coating.

[0023] Preferably, in steps S1 and S3, the coating amount of the adhesive is 6-8 g / m 2 , and the drying conditions are: 80-100 °C, 2-3 min; the components of the adhesive are as follows: polyvinyl alcohol 35-50 wt%, acrylate emulsion 20-40 wt%, solvent 10-20 wt%, crosslinking agent 3-5 wt%, thickening agent 0.5-1 wt%, dispersant 0.2-0.5 wt%;

[0024] In step S2, the coating amount of the thermosensitive agent is 5-7 g / m 2 , and the drying conditions are: 120-150 °C, 3-5 min;

[0025] In step S4, the coating amount of the protective agent is 3-5 g / m 2 , and the drying conditions are: 100-120 °C, 2-3 min.

[0026] Preferably, the components of the protective agent are as follows: adhesive 20-30 wt%, acrylic emulsion 10-15 wt%, ultraviolet absorber 2-5 wt%, antioxidant 1-2 wt%, and the balance is water. Among them, the ultraviolet absorber is preferably benzophenone, and the antioxidant is any one of antioxidant 300 (3-methyl-6-tert-butylphenol), BHA (butylhydroxyanisole), BHT (dibutylhydroxytoluene) and TBHQ (tert-butylhydroquinone). The components of the adhesive are as follows: polyvinyl alcohol 35-50 wt%, acrylate emulsion 20-40 wt%, solvent 10-20 wt%, crosslinking agent 3-5 wt%, thickening agent 0.5-1 wt%, dispersant 0.2-0.5 wt%.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. By adding AlN / CNT heat-conducting particles (aluminum nitride / carbon nanotube heat-conducting particles) to the thermosensitive coating to form a composite heat-conducting network to accelerate heat transfer (CNT can bridge the gaps between AlN particles to form a low thermal resistance network), the color development temperature threshold is reduced, and the color development is faster, more uniform and clearer; at the same time, the heat-conducting particles are uniformly dispersed in the thermosensitive coating by polydopamine coating and the bonding strength can be improved. The heat-conducting uniformity can reduce the phenomenon of thermal hysteresis and improve the sharpness of the printed line edge; moreover, the moisture resistance and oxidation resistance of AlN and the chemical inertness of CNT can cooperate to block the penetration of water and oxygen, and improve the durability in complex environments; the high modulus of CNT and the hardness of AlN can also cooperate to improve the scratch resistance of the coating;

[0029] 2. The adhesive can be used as the adhesive between the paper (paper base) / thermal-sensitive layer / protective layer, and also as the adhesive component in the thermal-sensitive layer and the protective layer, achieving multiple uses with one agent and reducing costs. At the same time, components such as acrylate emulsion and cross-linking agent in the adhesive can enhance the water resistance, abrasion resistance, heat resistance and chemical resistance of the thermal paper, while acrylic emulsion, ultraviolet absorber and antioxidant in the protective layer can improve the durability, water resistance and scratch resistance of the color display of the thermal paper under light. Detailed implementation mode

[0030] In the following examples, the preparation method of AlN / CNT thermal conductive particles includes the following steps:

[0031] Place 10 g of AlN powder in 150 ml of 3 M NaOH solution, ultrasonically treat for 2 h, centrifuge at 8000 rpm for 10 min, wash with deionized water until neutral, and then vacuum dry at 60 °C for 3 h to obtain hydroxylated AlN.

[0032] Place 5 g of CNT in 200 ml of mixed acid (volume ratio, concentrated H 2 SO 4 : concentrated HNO 3 = 3:1), reflux at 80 °C for 4 h, centrifuge at 5000 rpm for 15 min, wash with deionized water until neutral, and then vacuum dry at 60 °C for 5 h to obtain carboxylated CNT.

[0033] Disperse 5 g of hydroxylated AlN in 50 ml of ethanol solution containing 0.5 g of 3-aminopropyltriethoxysilane, react at 80 °C for 6 h, and obtain aminated AlN after centrifugation, washing and drying. Then, mix 5 g of aminated AlN with 3.75 g of carboxylated CNT and EDC / NHS cross-linking agent (1.15 g of EDC, 0.69 g of NHS, 50 ml of deionized water), stir at 500 rpm at room temperature for 12 h, and obtain amide bond-bonded AlN / CNT composite particles after centrifugation, washing, drying and pulverizing through a 200-mesh sieve.

[0034] Disperse 5 g of AlN / CNT composite particles in 500 ml of Tris-HCl buffer solution (pH = 8.5) containing dopamine hydrochloride (5 g), stir at 1000 rpm at room temperature for 10 h, then centrifuge at 3000 rpm for 10 min after completion, wash 3 times with deionized water, and then vacuum dry at 70 °C for 3 h to obtain AlN / CNT thermal conductive particles.

[0035] In Examples 1-3 and Comparative Examples 1-3, for the adhesive, ethanol was selected as the solvent, waterborne polyurethane was selected as the crosslinking agent, hydroxyethyl cellulose was selected as the thickener, and sodium polyacrylate was selected as the dispersant; in the protective layer, the adhesive was the adhesive used in the corresponding example, 2-hydroxy-4-methoxybenzophenone was selected as the ultraviolet absorber, and antioxidant 300 was used as the antioxidant stabilizer. The specific ratios are shown in Table 1.

[0036] Table 1 Ratios of the adhesive and each component of the protective layer used in Examples 1-3

[0037]

[0038] In Examples 1-3 and Comparative Examples 1-3, for the thermosensitive coating composition, 2-phenylamino-3-methyl-6-dibutylaminofluorane was selected as the colorless dye, p-hydroxybenzoic acid was selected as the developer, and bis(dimethylphenyl)ethane was selected as the thermosensitive sensitizer. The specific ratios are shown in Table 2.

[0039] Table 2 Ratios of each component in the thermosensitive coating composition used in Examples 1-3

[0040]

[0041] Example 1

[0042] The preparation method of the thermosensitive paper is as follows:

[0043] (1) Use high-quality degradable paper treated by calendering as the substrate. The paper base is dry and flat, and the moisture content is controlled at 5%.

[0044] (2) Uniformly coat the adhesive on the surface of the paper base, and the coating amount is 6 g / m 2 , and dry for 2 min in an environment at 100 °C;

[0045] (3) Mix the components in the thermosensitive coating composition and shear and disperse them with a high-speed shear machine for 15 min to prepare the thermosensitive coating;

[0046] (4) Uniformly coat the above thermosensitive coating on the surface of the adhesive coated in step (2), and the coating amount is 5 g / m 2 , and dry at 140 °C for 3 min after coating;

[0047] (5) Then uniformly coat the adhesive on the surface of the thermosensitive coating coated in step (4), and the coating amount is 6 g / m 2 , and dry for 2 min in an environment at 100 °C;

[0048] (6) Prepare the surface protection coating, and the ratio is shown in Table 1;

[0049] (7) Uniformly coat the protection coating on the surface of the thermosensitive layer coated in step (5), and the coating amount is 5 g / m2 , after coating, it is dried at 120 °C for 3 min.

[0050] Example 2

[0051] It is basically the same as Example 1, except that the weight part of AlN / CNT heat-conducting particles in the thermosensitive coating composition is 5 parts.

[0052] Example 3

[0053] It is basically the same as Example 1, except that the weight part of AlN / CNT heat-conducting particles in the thermosensitive coating composition is 6 parts.

[0054] Comparative Example 1

[0055] It is basically the same as Example 2, except that 5 weight parts of AlN powder are added to the thermosensitive coating composition.

[0056] Comparative Example 2

[0057] It is basically the same as Example 2, except that 5 weight parts of CNT powder are added to the thermosensitive coating composition.

[0058] Comparative Example 3

[0059] It is basically the same as Example 2, except that 5 weight parts of AlN / CNT composite particles are added to the thermosensitive coating composition and they are not coated with polydopamine.

[0060] Comparative Example 4

[0061] It is basically the same as Example 2, except that no adhesive is coated on the paper base surface.

[0062] Comparative Example 5

[0063] It is basically the same as Example 2, except that no adhesive is coated on the thermosensitive coating surface.

[0064] Comparative Example 6

[0065] It is basically the same as Example 2, except that no adhesive is coated on the paper base surface and the thermosensitive coating surface.

[0066] Use a thermal printer to print two-dimensional codes on the thermal papers prepared in Examples 1-3 and Comparative Examples 1-6. Use a decoder to detect the resolution, and observe the clear color development duration through detection. Observe the color development effect after the printed thermal paper is immersed in water for 12 hours; observe the color development effect after the printed thermal paper is placed in an environment of -4°C for 24 hours; observe the color development effect after applying edible oil on the surface of the color-developed thermal paper for 48 hours; test its stability under light. Use a xenon lamp to irradiate the printed thermal paper, control the power of the xenon lamp to be 1800W, and observe the color development effect after continuous irradiation at room temperature for 24 hours; detect the scratch resistance hardness according to the standard of GB / T6739-2006.

[0067] Table 3 Performance test results of thermal papers in Examples 1-3 and Comparative Examples 1-6

[0068]

[0069] It can be seen from the data comparison in Table 3 that the resolution of color development of the thermal paper prepared with AlN / CNT heat-conducting particles as components of the thermal coating composition is further improved, and the clear color development duration is also significantly extended. After using the multi-layer adhesive, the stability of the thermal paper in complex use environments such as water immersion, cold, greasy, and light is significantly improved, and the surface strength is greatly enhanced. The effect of adding a multi-layer adhesive between the paper base / thermal layer and the thermal layer / protective layer is more advantageous in cold and greasy environments.

[0070] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A heat-sensitive coating composition, characterized in that: The invention comprises the following components in parts by weight: 9-15 parts of colorless dye, 27-30 parts of developer, 10-12 parts of adhesive, 8-10 parts of thermosensitive sensitizer, 5-8 parts of water and 2-8 parts of AlN / CNT thermal conductive particles; wherein the AlN / CNT thermal conductive particles comprise an AlN / CNT composite particle inner core bonded by amide bonds and a PDA shell layer coated outside the inner core.

2. The heat-sensitive coating composition according to claim 1, characterized in that: The preparation method of AlN / CNT thermal conductive particles is: firstly hydroxylating AlN and carboxylating CNT; The hydroxylated AlN is then dispersed in a solution containing aminosiloxane, heated for reaction, centrifuged, washed, and dried. Amination AlN is obtained; Then, the amino AlN is mixed with the carboxylated CNT and the EDC / NHS crosslinking agent, stirred for reaction, centrifuged, washed, dried, crushed and sieved to obtain amide bonded AlN / CNT composite particles; Finally, the AlN / CNT composite particles are dispersed in a dopamine hydrochloride buffer solution, stirred, centrifuged, washed, and dried.

3. The heat-sensitive coating composition according to claim 2, characterized in that: The addition ratio of hydroxylated AlN to aminosiloxane, carboxylated CNT and EDC / NHS crosslinker is (2-10) g: (0.2-2) g: (1-5) g: (40-100) ml; Wherein, the molar ratio of EDC to NHS in the EDC / NHS cross-linking agent is 1:(0.5-1.5).

4. The heat-sensitive coating composition according to claim 2, characterized in that: The aminosiloxane is 3-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

5. The heat-sensitive coating composition according to claim 2, characterized in that: The conditions for the heating reaction are: 60-90°C, 4-8h; The stirring reaction conditions are: room temperature, 300-1000 rpm, 8-15 h.

6. The heat-sensitive coating composition according to claim 2, characterized in that: The concentration of dopamine hydrochloride is 5-20 g / L, and the dosage ratio of AlN / CNT composite particles to dopamine hydrochloride buffer is (3-10) g: (300-1000) ml.

7. The heat-sensitive coating composition according to claim 1, characterized in that: The components of the adhesive are as follows: 35-50wt% of polyvinyl alcohol, 20-40wt% of acrylate emulsion, 10-20wt% of solvent, 3-5wt% of crosslinking agent, 0.5-1wt% of thickener, and 0.2-0.5wt% of dispersant.

8. Use of the heat-sensitive coating composition according to any one of claims 1 to 7 in the preparation of heat-sensitive paper, characterized in that: The steps include: S1, applying an adhesive on a paper base and drying it to form an inner adhesive layer; S2, coating the heat-sensitive agent prepared from the heat-sensitive coating composition on the surface of the inner adhesive layer and drying it to form a heat-sensitive coating; S3, then apply another layer of adhesive on the surface of the heat-sensitive coating and dry it to form an outer adhesive layer; S4. Finally, a protective agent is applied to the outer adhesive layer and dried to form a protective coating.

9. The use according to claim 8, characterized in that: In steps S1 and S3, the coating amount of the adhesive is 6-8 g / m 2 , Drying conditions: 80-100°C, 2-3min; In step S2, the coating amount of the thermosensitive agent is 5-7 g / m 2 , drying conditions are: 120-150℃, 3-5min; In step S4, the coating amount of the protective agent is 3-5 g / m 2 The drying conditions are: 100-120℃, 2-3min.

10. The use according to claim 8, characterized in that: The components of the protective agent are as follows: 20-30wt% of adhesive, 10-15wt% of acrylic emulsion, 2-5wt% of ultraviolet absorber, 1-2wt% of antioxidant, and the balance is water.